Characteristics of Low Back Pain in Medical Students of Muhammadiyah Jakarta University Class of 2019 After Online Class for One Semester - Rizkiandini, Sulfa; Hamzah, Zainy (Talenta Universitas Sumatera Utara, 2023)
Introduction: Lower back pain (LBP) is a complaint that is often felt by everyone in everyday life. In 2010 the Global Burden of Disease Study estimated low back pain to be one of the top ten diseases and injuries with the highest number in the world. According to research conducted by Altinel in 2008, about 62% of adults experience LBP as a result of sitting too long in the wrong position. The wrong sitting attitude of someone at work will affect the unfavorable results of their work. Method: This research is a descriptive analytic survey research, which aims to know about low back pain ofÂ the students of the Medical Education Study Program Class of 2019. approach used in this study is